Some 'Conceptualizing' on Goodwill. - Gynther, Reg S. (The Accounting Review, 1969)
In the discipline of accounting, "goodwill" has been a thorny problem. A lot of people from all walk of life have tried their hands in defining goodwill but still they could not give a universal definition. The main cause of the arguments seems to be that the real nature of Goodwill has been submerged in the literature by the methods that we have been forced to use in practice when calculating the total values of entities. Goodwill exists because assets are present, even though they are not listed with the tangible assets. For example, "special skill and knowledge," "high managerial ability," "monopolistic situation," "social and business connections," "good name and reputation," "favorable situation," "excellent staff," "trade names" and "established clientele" are assets in this category. In the valuing process, each asset would be valued by discounting all of the net future cash flows that it was expected to create, irrespective of whether or not these indicated excess profits, or normal profits, or low profits, or losses.